ANALYSIS OF ARTICLE 21 INCOME TAX CALCULATIONS AND DEDUCTIONS ON EMPLOYEE SALARIES AT PT BTx - Kevin Julian Depthios; Anjaling Anjaling; Dian Aprilia Eleuwarin; Dion Alpandy S.S; Afian Dezi Sanda Sipi (Jurnal Ekonomi, 2023)
This study entitled "Analysis of Article 21 Income Tax Calculations and Deductions on Employee Salaries at PT Bumiputera Banzai", Has a problem formulation How to calculate income tax article 21 and withholding income tax article 21 on employee salaries at PT BTx. The purpose of this study was to analyze the calculation of income tax article 21 and withholding tax article 21 on employee salaries at PT BTx. The data analysis method used in this study is descriptive analysis with the stages of collecting and calculating permanent employee salaries in 2022, analyzing the calculation and withholding of income tax article 21, and drawing conclusions from the results of the analysis. The type of data used in this study is qualitative data sourced from primary data derived from observation, interviews and documentation to draw conclusions and compare theories to support the results in the research. Based on the analysis carried out, the results of the data analysis lead to the conclusion that the calculation of income tax article 21 and withholding income tax article 21 with informants who are employees of the consulting office that handles the company PT BTx are in accordance with the applicable tax regulations. With this, PT Bumiputera Banzai already understands how to calculate and deduct article 21 income tax on their permanent employees.